A porous carbon-loaded interlayer-space-expanded molybdenum disulfide composite and its preparation method and application
By using the preparation method of expanding the molybdenum disulfide composite with porous carbon-loaded layer spacing in the negative electrode material of sodium ion battery, the problems of molybdenum disulfide volume expansion and poor conductivity are solved, and a negative electrode material with high reversible capacity and excellent electrochemical performance are achieved.
Patent Information
- Application Number
- CN202211157338.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-22
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-09-22
AI Technical Summary
The existing sodium ion battery negative electrode material molybdenum disulfide has problems of large volume expansion and poor conductivity, which leads to the failure of its electrochemical performance to meet expectations.
The preparation method of the porous carbon-supported layer spacing expansion molybdenum disulfide composite is adopted. Through the hydrothermal and calcining process, the ionic liquid is used to dissolve the biomass, which promotes the spacing expansion of the molybdenum disulfide layer spacing, and uses porous carbon as a carbon matrix to form a cladding layer to improve conductivity.
The high reversible specific capacity, good cycle stability and excellent electrochemical properties of the negative electrode material of sodium ion battery are achieved, and volume expansion and structural strain are avoided.
Smart Images

Figure CN115472797B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a porous carbon-loaded interlayer-spaced expanded molybdenum disulfide composite and a preparation method and application thereof. Background Art
[0002] With the growing demand for renewable energy utilization, secondary batteries have ushered in new opportunities in the energy revolution. Among them, the global production and manufacturing scale of lithium-ion batteries has reached an unprecedented level and has taken a leading position. However, due to the limited reserves of lithium elements, lithium-ion batteries cannot meet the needs of large-scale application of grid-level energy storage. Sodium resources are abundant and low-cost in nature. At the same time, sodium-ion batteries have the advantages of wide temperature range adaptability and high safety. Therefore, they have attracted much attention as the next generation of batteries. Among the many sodium-ion battery negative electrode materials, the conversion-type two-dimensional molybdenum disulfide-based negative electrode has the advantages of low cost and relatively high capacity. The layered structure of molybdenum disulfide has weak van der Waals force and large interlayer distance (0.615nm), which can also effectively promote the storage of sodium, but it also has the disadvantages of large volume expansion and poor conductivity. At present, the improvement strategies of MoS2 negative electrode can be divided into three levels. The first is the atomic level, such as introducing surface defects, expanding interlayer spacing, phase control, heteroatom doping, etc., which can effectively improve the sodium conductivity and sodium ion diffusion dynamics; the second is the nano level, combining the MoS2 nanostructure with a stable and highly conductive carbon base to alleviate volume expansion and structural strain and accelerate electron transport; the third is at the macro level, constructing an independent negative electrode without using conductive agents and binders, which has significant advantages such as easy manufacturing, good flexibility and strong structure.
[0003] In recent years, amorphous carbon has attracted extensive attention as a promising negative electrode for sodium-ion batteries. Amorphous carbon has a vortex carbon structure with appropriate porosity, which is conducive to the rapid diffusion and reversible storage of sodium ions. Amorphous carbon with a large specific surface area, such as porous carbon, electrospun carbon nanofibers, hollow carbon nanowires and hollow carbon nanospheres, has good rate performance and high capacity due to the large number of active sites provided by the high porosity. However, due to the continuous formation of the solid electrolyte phase interface film, the high specific surface area instead causes low initial coulombic efficiency and poor cycle stability, making the electrochemical performance of these carbons unable to meet expectations. Summary of the invention
[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for preparing a porous carbon-loaded molybdenum disulfide composite with expanded interlayer spacing, which can be used as the negative electrode of a sodium ion battery to improve the performance of the sodium ion battery.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a porous carbon-supported interlayer-space expanded molybdenum disulfide composite (PC@MoS2@ICC) comprises the following steps:
[0007] (1) dissolving sodium molybdate and thioacetamide in water to form a solution, then adding activated carbon and polyvinyl pyrrolidone to the solution, stirring evenly and ultrasonicating to obtain a black suspension;
[0008] (2) transferring all the black suspension obtained in step (1) into a reaction vessel for hydrothermal reaction;
[0009] (3) grinding the product obtained from the hydrothermal reaction in step (2) and the biomass sufficiently, and then mixing and stirring the mixture with the ionic liquid to obtain a black viscous liquid;
[0010] (4) calcining the black viscous liquid obtained in step (3), and washing, drying and grinding the product to obtain a product.
[0011] Specifically, in step (1), the mass ratio of activated carbon, sodium molybdate and thioacetamide is (0.5-2.5):1:1, and the preferred mass ratio is 0.75:1:1; the mass ratio of the added polyvinyl pyrrolidone to the activated carbon is (0.02-0.1):1, and the preferred mass ratio is 0.05:1; the stirring time is 0.5-3h, and the ultrasonic time is 0.5-3h.
[0012] Specifically, in step (2), the hydrothermal reaction conditions are to keep the temperature at 190-220° C. for 20-30 h, preferably at 200° C. for 24 h.
[0013] Specifically, in step (3), the biomass is selected from any one or a combination of two or more of waste wood chips, straw, corn stalks, rice husks, bagasse, cellulose, lignin, and cotton.
[0014] Specifically, in the ionic liquid, the cation is selected from any one of alkyl imidazole, alkyl pyridine or dialkyl imidazole quaternary ammonium salt, and the anion is selected from any one of dihydrogen phosphate, ferric chloride ion or acetate.
[0015] Specifically, in step (3), the mass ratio of biomass, hydrothermal product and ionic liquid is (1-2):1:(3-4), preferably 1:1:3; the mixing and stirring time is 6-10 hours, preferably 8 hours.
[0016] Specifically, in step (4), calcination is carried out under argon protection, the temperature is increased to 700-1000°C at a heating rate of 1-10°C / min, and the temperature is kept at 2-6h, and then cooled to room temperature at a cooling rate of 5-10°C / min. Preferably, the heating rate is 5°C / min, the holding temperature is 1000°C, the holding time is 3h, and the cooling rate is 10°C / min.
[0017] Specifically, in step (4), washing is performed by alternately rinsing with acetone and distilled water; drying is performed by vacuum drying at 105° C. for 8 to 16 hours; grinding time is 0.5 to 3 hours, and the powder particle size after sieving is less than 100 mesh.
[0018] Furthermore, the porous carbon-loaded interlayer-space expanded molybdenum disulfide composite prepared by the above preparation method is also within the protection scope of the present invention.
[0019] Furthermore, the present invention also claims to protect the use of the above-mentioned porous carbon-loaded interlayer spacing expanded molybdenum disulfide composite as a negative electrode material for sodium ion batteries.
[0020] Furthermore, the present invention also claims protection for a sodium ion battery, the negative electrode of which is prepared by using the above-mentioned porous carbon-loaded interlayer expansion molybdenum disulfide composite.
[0021] Beneficial effects:
[0022] (1) The present invention utilizes ionic liquid to dissolve biomass. During the calcination process, more stable pyridine rings enter the molecular layer of molybdenum disulfide, attracting alkyl fragments to undergo carbon recombination, thereby expanding the interlayer spacing of molybdenum disulfide. On the one hand, it provides a new utilization pathway for ionic liquids, and on the other hand, it provides a new method for structural adjustment of molybdenum disulfide.
[0023] (2) The present invention uses porous carbon as the carbon matrix, and ionic liquid-derived carbon forms a coating layer on its surface, which promotes the transformation of open pores on the surface into closed pores and provides strong conductivity, which is beneficial to providing more reversible sodium capacity.
[0024] (3) The present invention prepares the desired porous carbon-loaded interlayer-space expanded molybdenum disulfide composite by a hydrothermal and calcination method, does not require other chemical synthesis methods, does not produce toxic gases, and is environmentally friendly.
[0025] (4) As a negative electrode material for sodium ion batteries, the product of the present invention has a high reversible specific capacity, good cycle stability and excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0027] Figure 1 This is a scanning electron microscope (2 μm) of the sodium ion battery negative electrode material prepared in Example 1.
[0028] Figure 2 This is a transmission electron micrograph (50 nm) of the sodium ion battery negative electrode material prepared in Example 1.
[0029] Figure 3 X-ray diffraction patterns of Example 1 (PC@MoS2@ICC), Comparative Example 1 (MoS2@ICC), Comparative Example 2 (PC@MoS2) and molybdenum disulfide.
[0030] Figure 4 These are the X-ray diffraction patterns of Example 1 (PC@MoS2@ICC), Example 2 (PC@MoS2@ICC-2), Example 3 (PC@MoS2@ICC-3) and Example 4 (PC@MoS2@ICC-4).
[0031] Figure 5 This is the nitrogen desorption curve of Example 1 (PC@MoS2@ICC) and porous carbon (PC).
[0032] Figure 6 The charge and discharge curves of the sodium ion battery prepared in Example 1 at a current density of 0.1 A / g after three initial charge and discharge cycles.
[0033] Figure 7 The sodium ion battery prepared in Example 1 was charged and discharged three times at a current density of 0.1 A / g, and then cycled 250 times.
[0034] Figure 8 The sodium ion battery prepared in Example 1 was charged and discharged three times at a current density of 0.1 A / g, and then cycled 1000 times at a current density of 1 A / g.
[0035] Fig. 9 The impedance spectrum of the sodium ion battery negative electrode material and molybdenum disulfide prepared in Example 1 at a frequency of 100000 to 0.01 Hz after 50 charge and discharge cycles. DETAILED DESCRIPTION
[0036] The present invention can be better understood with reference to the following examples.
[0037] Example 1
[0038] Take 1.5g of sodium molybdate and thioacetamide, dissolve them in 70ml of distilled water, add 2g of activated carbon and 0.1g of polyvinyl pyrrolidone to the clear solution, stir thoroughly and ultrasonicate for 0.5h, then transfer completely to the inner lining of a 100ml polytetrafluoroethylene reactor. Carry out hydrothermal reaction in the reactor, and keep it at a temperature of 200℃ for 24h. The hydrothermal product is filtered, rinsed, dried, and mixed with microcrystalline cellulose in a mass ratio of 1:1. Add ionic liquid at a mass ratio of 1:3 between microcrystalline cellulose and ionic liquid (1-butyl-3-methylimidazolium acetate). After mixing and stirring for 8h, transfer to a boat, calcine in a tubular furnace, use argon as protective gas, heat up to 1000℃ at 5℃ / min, and keep it for 3h, then cool down to room temperature at 10℃ / min, take out the sample, wash, filter, and dry, and grind to obtain the negative electrode material (PC@MoS2@ICC) of sodium ion battery.
[0039] Example 2
[0040] Take 1.5g of sodium molybdate and thioacetamide, dissolve them in 70ml of distilled water, add 2g of activated carbon and 0.1g of polyvinyl pyrrolidone to the clear solution, stir thoroughly and ultrasonicate for 0.5h, then transfer completely to the 100ml polytetrafluoroethylene reactor lining. Carry out hydrothermal reaction in the reactor, and keep it at a temperature of 220℃ for 20h. The hydrothermal product is filtered, rinsed, dried, mixed with microcrystalline cellulose in a mass ratio of 1:1, and then added with ionic liquid (1-butyl-3-methylimidazole dihydrogen phosphate) in a mass ratio of 1:3. After mixing and stirring for 8h, transfer to the boat, calcine in a tubular furnace, use argon as protective gas, heat to 700℃ at 5℃ / min and keep it for 2h, then cool to room temperature at 10℃ / min, take out the sample, wash, filter and dry, and grind to obtain the negative electrode material (PC@MoS2@ICC-2) of sodium ion battery.
[0041] Example 3
[0042] Take 1.5g of sodium molybdate and thioacetamide, dissolve them in 70ml of distilled water, add 2g of activated carbon and 0.1g of polyvinyl pyrrolidone to the clear solution, stir thoroughly and ultrasonicate for 0.5h, then transfer completely to the 100ml polytetrafluoroethylene reactor lining. Carry out hydrothermal reaction in the reactor, and keep it at a temperature of 200℃ for 24h. The hydrothermal product is filtered, rinsed, dried, mixed with wood powder in a mass ratio of 2:1, and then added with ionic liquid (1-butyl-3-methylimidazolium acetate) in a mass ratio of 1:3. After mixing and stirring for 8h, transfer to the boat, calcine in a tube furnace, use argon as protective gas, heat up to 1000℃ at 5℃ / min, keep it for 6h, then cool down to room temperature at 10℃ / min, take out the sample, wash, filter and dry, and grind to obtain the negative electrode material (PC@MoS2@ICC-3) of sodium ion battery.
[0043] Example 4
[0044] Take 1.5g of sodium molybdate and thioacetamide, dissolve them in 70ml of distilled water, add 2g of activated carbon and 0.1g of polyvinyl pyrrolidone to the clear solution, stir thoroughly and ultrasonicate for 0.5h, then transfer them completely to the 100ml polytetrafluoroethylene reactor lining. Carry out hydrothermal reaction in the reactor, and keep it at a temperature of 190℃ for 30h. The hydrothermal product is filtered, rinsed, dried, mixed with microcrystalline cellulose at a mass ratio of 2:3, and then added with ionic liquid (1-butyl-3-methylimidazole dihydrogen phosphate) at a mass ratio of 1:3. After mixing and stirring for 8h, transfer it to a boat, calcine it in a tubular furnace, use argon as protective gas, heat it to 1000℃ at 5℃ / min and keep it for 3h, then cool it to room temperature at 10℃ / min, take out the sample, wash, filter and dry it, and grind it to obtain the negative electrode material (PC@MoS2@ICC-4) of sodium ion battery.
[0045] Comparative Example 1
[0046] Take 1.5g of sodium molybdate and thioacetamide, dissolve them in 70ml of distilled water, and transfer the clear solution completely to a 100ml polytetrafluoroethylene reactor liner. Carry out a hydrothermal reaction in the reactor and keep it at a temperature of 200℃ for 24h. The hydrothermal product is filtered, rinsed, dried and mixed with an equal mass of microcrystalline cellulose. The ionic liquid is added at a mass ratio of 1:3 between microcrystalline cellulose and ionic liquid (1-butyl-3-methylimidazolium acetate). After mixing and stirring for 8h, transfer it to a boat and calcine it in a tubular furnace. With argon as the protective gas, heat it to 1000℃ at 5℃ / min and keep it for 3h, then cool it to room temperature at 10℃ / min. Take out the sample, wash, filter and dry it, and grind it to obtain the negative electrode material (MoS2@ICC) of the sodium ion battery.
[0047] Comparative Example 2
[0048] Take 1.5g of sodium molybdate and thioacetamide, dissolve them in 70ml of distilled water, add 2g of activated carbon and 0.1g of polyvinyl pyrrolidone to the clear solution, and transfer them completely to the 100ml polytetrafluoroethylene reactor lining after sufficient stirring and ultrasonic treatment for 0.5h. Carry out hydrothermal reaction in the reactor and keep it at 200℃ for 24h. The hydrothermal product is filtered and rinsed, and then transferred to a boat after drying. It is calcined in a tubular furnace, with argon as the protective gas, and the temperature is raised to 1000℃ at 5℃ / min for 3h, then cooled to room temperature at 10℃ / min. Take out the sample, wash, filter and dry it, and grind it to obtain the negative electrode material (PC@MoS2) for sodium ion batteries.
[0049] Example 5
[0050] The sodium ion battery negative electrode materials prepared in Examples 1, 2, 3, 4 and Comparative Examples 1 and 2 were mixed with conductive agent acetylene black and polyvinyl difluoride at a mass ratio of 8:1:1, and the mixture was prepared into a slurry with N-methylpyrrolidone, and applied to a copper foil. The prepared slurry coating was placed in a vacuum drying oven and dried at 90°C for 24 hours. A circular electrode with a diameter of 12 mm was pressed out with a tablet press to obtain an experimental battery negative electrode, with a sodium sheet as the counter electrode, a glass fiber disc as the diaphragm, an organic solution of sodium perchlorate as the electrolyte, and a spring and a gasket were added to assemble a 2032 model button battery in a glove box.
[0051] Figure 1 This is a scanning electron microscope image of the sodium ion battery negative electrode material prepared in Example 1. It can be seen that the surface of the material is flat and has no obvious holes. Figure 2 The transmission electron microscope can clearly show the layered structure of molybdenum disulfide after the interlayer spacing has expanded from the original 0.62nm to the current 1.01nm. The expansion of the interlayer spacing can accommodate more sodium ions and promote the migration of sodium ions between the layers. The combination of carbon and the expansion of the interlayer spacing of molybdenum disulfide can effectively optimize the conductivity of the negative electrode material and the diffusion of sodium ions. Figure 3 The comparison of X-ray diffraction patterns (XRD) can clearly show the process of interlayer spacing expansion. For samples with ionic liquid biomass-derived carbon (ICC) added, the position of the characteristic peak of the MoS2 002 crystal plane shifts significantly and turns to a smaller diffraction angle position, indicating the process of interlayer spacing expansion. Figure 4 The XRD diagrams of Examples 1-4 show that the interlayer spacing of molybdenum disulfide is expanded in the other three examples, and Examples 1 and 4 have wider interlayer spacing. Figure 5 The adsorption-desorption curves of Example 1 and porous carbon (PC) are shown. After calculation and comparison, the specific surface area of Example 1 is 6.29 m2 / g, which is significantly smaller than the 36.38m / g of porous carbon. 2 / g, indicating that the pores on the porous carbon surface are covered by the carbon layer and transformed into closed pores.
[0052] like Figure 6 As shown, it was determined that when the sample of Example 1 was used as the electrode material, the discharge capacity of the sodium ion battery at a current density of 0.1 A / g was 1024.91 mAh / g, and the initial coulombic efficiency was 62.36%. Figure 7 In the experiment, the electrode material retained a mass specific capacity of 480.75 mAh / g after 250 charge and discharge cycles at a current density of 0.1 A / g, while when molybdenum disulfide was used as an electrode, it only retained a mass specific capacity of 203 mAh / g after 250 charge and discharge cycles at the same current density. Figure 8 In the experiment, the electrode material was charged and discharged 1000 times at a high current density of 1A / g, maintaining a mass specific capacity of 220.47mAh / g and a capacity retention rate of 81.96%, far exceeding the capacity retention rate of 20.87% of molybdenum disulfide under the same conditions. Fig. 9 Comparing the AC impedance of Example 1 with that of molybdenum disulfide, it is obvious that under the influence of the carbon carrier and the enlarged interlayer spacing, the electron diffusion is greatly improved and the conductive performance is significantly improved.
[0053] The present invention provides a porous carbon-supported interlayer spacing expanded molybdenum disulfide composite and its preparation method and application ideas and methods. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A method for preparing a porous carbon-supported molybdenum disulfide composite with expanded interlayer spacing, characterized in that: The steps include: (1) Sodium molybdate and thioacetamide are dissolved in water to form a solution, and then activated carbon and polyvinyl pyrrolidone are added to the solution, stirred evenly and subjected to ultrasound to obtain a black suspension; (2) transferring all the black suspension obtained in step (1) into a reaction vessel for hydrothermal reaction; (3) The product obtained from the hydrothermal reaction in step (2) is fully ground with the biomass, and then mixed with the ionic liquid and stirred to obtain a black viscous liquid; (4) calcining the black viscous liquid obtained in step (3), and washing, drying and grinding the product to obtain a product; In step (3), in the ionic liquid, the cation is selected from any one of alkyl imidazole, alkyl pyridine or dialkyl imidazole quaternary ammonium salt, and the anion is selected from any one of dihydrogen phosphate, ferric chloride ion or acetate.
2. The method for preparing the porous carbon-supported molybdenum disulfide composite with expanded interlayer spacing according to claim 1, characterized in that: In step (1), the mass ratio of activated carbon, sodium molybdate and thioacetamide is (0.5-2.5):1:1, and the mass ratio of added polyvinyl pyrrolidone to activated carbon is (0.02-0.1):1; the stirring time is 0.5-3 h, and the ultrasonic time is 0.5-3 h.
3. The method for preparing the porous carbon-supported molybdenum disulfide composite with expanded interlayer spacing according to claim 1, characterized in that: In step (2), the hydrothermal reaction conditions are to keep the temperature at 190-220° C. for 20-30 hours.
4. The method for preparing the porous carbon-supported molybdenum disulfide composite with expanded interlayer spacing according to claim 1, characterized in that: In step (3), the biomass is selected from any one or a combination of two or more of waste wood chips, straw, corn stalks, rice husks, bagasse, cellulose, lignin, and cotton.
5. The method for preparing the porous carbon-supported molybdenum disulfide composite with expanded interlayer spacing according to claim 1, characterized in that: In step (3), the mass ratio of biomass, hydrothermal product and ionic liquid is (1-2):1:(3-4), and the mixing and stirring time is 6-10 hours.
6. The method for preparing the porous carbon-supported molybdenum disulfide composite with expanded interlayer spacing according to claim 1, characterized in that: In step (4), calcination is carried out under argon protection, the temperature is increased to 700-1000°C at a heating rate of 1-10°C / min, and the temperature is kept at that temperature for 2-6 hours, and then the temperature is cooled to room temperature at a cooling rate of 5-10°C / min.
7. The method for preparing the porous carbon-supported molybdenum disulfide composite with expanded interlayer spacing according to claim 1, characterized in that: In step (4), washing is performed by rinsing with acetone and distilled water at intervals; drying is performed by vacuum drying at 105° C. for 8 to 16 hours; grinding time is 0.5 to 3 hours, and the powder particle size after sieving is less than 100 mesh.
8. The porous carbon-supported molybdenum disulfide composite with expanded interlayer spacing prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the porous carbon-supported interlayer-space expanded molybdenum disulfide composite as claimed in claim 8 as a negative electrode material for sodium ion batteries.
10. A sodium ion battery, characterized in that: The negative electrode is prepared by using the porous carbon-loaded interlayer-space expanded molybdenum disulfide composite described in claim 8.
Citation Information
Patent Citations
Metal sulfide / carbon composite material, preparation method of the same, and application of the same in cell cathode materials
CN109546139A
Carbon-coated mesoporous transition metal sulfide negative electrode material as well as preparation method and application thereof
CN112768656A